Islands on Fire? Navigating Ambiguity and Space during the 1821 Greek Revolution in the Aegean Sea - Gekas, Sakis (Historein, 2023)
This article focuses on some aspects of the fascinating histories of islands in the Aegean and the Ionian seas during the Greek Revolution, drawing on documents of the time and histories of the revolution written during or soon after the big event. It looks at the dynamics of the revolution, as seen in the changing perceptions of space in the Aegean Archipelago and the Ionian Seas. It suggests ways to follow the “conceptual or political turn” and the “spatial” turn in the history of the revolution, and argues for exploring the political, fiscal and maritime territorialisation that took place, and by historicising the ambiguity that prevailed during the revolution.